Examining gender differences in the correlates of psychopathy: A systematic review of emotional, cognitive, and morality-related constructs. (July 2018) - Efferson, Leah M.; Glenn, Andrea L.
Abstract: Previous research examining the correlates of psychopathy has often focused on males. However, research on female psychopathy has increased over the past twenty years, and we are gaining more information about the similarities and differences in psychopathy in males and females. The purpose of this systematic review is to discuss the current research on gender differences in the correlates of psychopathy. The research to date largely relies on measures based on the Psychopathy-Checklist-Revised and includes studies examining various types of emotional and cognitive processes, as well as moral judgment, a construct involving both emotional and cognitive processing. Research suggests that both males and females higher in psychopathy show similar deficits in emotional modulation of the startle reflex, but females do not display some of the emotional processing deficits to the same extent as males higher in psychopathy. Because of limited research, it is less clear if there are gender differences in the relationship between psychopathy and cognitive processes. Females with psychopathic traits have not been found to demonstrate response perseveration or passive avoidance errors, but the relationship between psychopathy and other cognitive processes such as error processing seems to be similar in males and females. There also may be differences in how males and females higher in psychopathy process moral information, including how they respond to unfairness and moral violations. More studies directly comparing males and females within the same sample are needed to further examine gender differences in the correlates of psychopathy. Highlights: Females with psychopathic traits do not display some emotional processing deficits to the same extent as males. Females with psychopathic traits do not demonstrate response perseveration or passive avoidance errors like males. Males and females with psychopathic traits respond differently to unfairness and moral violations